The Late Intermediate Period in Cajamarquilla from the evidence of the Tello sector - Huaman Santillán, Yomira Silvia (2021)
This research project addresses the problem of the occupation of the Late Intermediate Period in the archaeological site of Cajamarquilla, located within the city of Metropolitan Lima, one of the most extensive settlements on the coast of Lima, but at the same time one of the less researched. The present study seeks to define the importance that Cajamarquilla acquired during this period, from the analysis of the architecture of mud walls that appear on the surface, the spatial distribution of the architectural units, their functionality. With the result of this research work, it will be possible to have a greater knowledge about the cultural practices developed in late pre-Hispanic periods in Cajamarquilla, their interactions with other sites in the Rímac valley, the productive strategies they had and the hierarchical situation at the time of arrival. of the Incas and the annexation of this territory to the Tawantinsuyu.